Inovasi Produk Kulit Pisang Berbasis Zero Waste sebagai upaya Pemberdayaan Digital di Komunitas Nasyiatul Aisyiyah Sidenreng Rappang - Yaya, Astrina Nur Inayah; Herman, Bahtiar; Aksan, Muhammad; Zahilah, Riska Nur; Irnandi, Erwin; Reskianti, Reskianti; Yuliana , Yuliana (Jurnal SOLMA, 2025)
Background: Nasyiatul Aisyiyah (NA) Sidenreng Rappang which is a women's wing organization of Muhammadiyah which focuses on empowering women and young people. The problems that occur with Nasyiatul Aisyiyah are (1) they still lack knowledge zero waste product innovation; (2) limited access  digital marketing technology; (3) low competitiveness of local products. Objectives (1) increase members' understanding and skills in processing banana peels into innovative and economically valuable products; (2) Increase members' ability to use digital marketing to market zero waste products more widely and effectively. (3) Building an online marketing network that can increase product competitiveness in local markets. The partner for this service activity is the Nasyiatul Aisyiyah group with 30 participants. Method: The stages in this activity are: (a) Preparation stage which consists of surveys and discussions with partners, preparation of training materials and production. This stage was carried out by FGD with the NA leadership and PKM team members; (b) The implementation phase is carried out over two days, namely. First day of activity opening, pre-test, delivery of material, practical demonstration of developing zero waste products from banana peels, discussion and post-test, closing of activities; Second day of digital marketing and e-commerce training activities as well as branding and packaging creation (c) Service program evaluation stage.  Results: This activity are an increase in knowledge which can be seen from NA's activeness in the activity. Conclusion: the implementation of the activity went smoothly and the participants were very enthusiastic in taking part in the activity.